Two new species of Utivarachna Kishida, 1940 from southern China, with an updated key to the Chinese species (Araneae: Trachelidae) - Liu, Keke; Yin, Haiqiang; Haddad, Charles R.; Xu, Xiang; Ma, Zhining (Zootaxa, 2020)
Two new trachelid spiders were collected from Guangxi, southern China, and are described here as Utivarachna subfabaria sp. nov. (♂, ♀) and U. tangi sp. nov. (♀). Both species belong to the Utivarachna kinabaluensis-group. Detailed generic synapomorphies are deduced based on an assessment of all known Utivarachna species, and an updated key to the Utivarachna species from China is provided.